Mechanical Differential Mathematical Model - Frantisek Brumercik; Michal Lukac; Aleksander Nieoczym (Communications - Scientific letters of the University of Zilina, 2015)
The simulation of a road vehicle requires also the model of a mechanical differential. This article describes one of the possibilities how to build a mechanical differential model by the selected vehicle model structure.